Digital insights: bridging the phenotype-to-genotype divide. (2nd April 2021) - McCabe, Matthew F; Tester, Mark
Abstract : This article comments on: Han R, Wong AJY, Tang Z, Truco MJ, Lavelle DO, Kozik A, Jin Y, Michelmore R . 2021. Drone phenotyping and machine learning enable discovery of loci regulating daily floral opening in lettuce. Journal of Experimental Botany 72, 2979–2994 .